Near-Field Light-Bending Photonic Switch: Physics of Switching Based on Three-Dimensional Poynting Vector Analysis; Photonics; Vol. 9, iss. 3 - Yue Liyang; Wang Zengbo; Yan Bing; Xie Yao; Гейнц Ю. Э. Юрий Эльмарович; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2022, 2022)
Title screen